(3OjhGf GHf GdaGQVs - (3GHf GdaGQV, YeQ Hf Ydj Hf eQTO, J(B632(3g`s ((3Ydj Hf jhSa Hf CMeO CHh Sdje GdTGaYj GdQaGYjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj GNJU MHjHg GdCSfi HebGe bGH bhSjf Ch COfi bGd GdabjQYeQ Hf GdaGQV (B: (3SGFb GdCUaGf jWhj GdHjWi (B*** (3efYeG YQL Ydi cKHGf Wjs
(3BNQgG (B:s
(3aj MGdI GdHYO QhMj cfJ CQSdgG (B*** (3JbHd GdCQV Yfj agj fGFjJj , hgPg fhHI GdCTHGM bO MVQJ (B*** (3aGeOO jefc dj JMVj HgG TaJjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 55s
(3eYLe GdeDdajf(B: 2 / 568s
(3cTa GdXfhf(B: 1 / 767s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs